2013
DOI: 10.1007/s11356-013-1862-z
|View full text |Cite
|
Sign up to set email alerts
|

Chiral profiling of azole antifungals in municipal wastewater and recipient rivers of the Pearl River Delta, China

Abstract: Enantiomeric compositions and fractions (EFs) of three chiral imidazole (econazole, ketoconazole, and miconazole) and one chiral triazole (tebuconazole) antifungals were investigated in wastewater, river water, and bed sediment of the Pearl River Delta, South China. The imidazole pharmaceuticals in the untreated wastewater were racemic to weakly nonracemic (EFs of 0.450-0.530) and showed weak enantioselectivity during treatment in the sewage treatment plant. The EFs of the dissolved azole antifungals were usua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 40 publications
(49 reference statements)
2
16
0
1
Order By: Relevance
“…The other azole anti-fungals were all only occasionally detected and at very low concentrations (Table 1). This pattern was similar to that in the water of the Pearl River (Huang et al, 2013). However, the presence of the azole anti-fungals in groundwater has rarely been reported worldwide, precluding further discussion or comparison (Table 1).…”
Section: Azole Anti-fungalssupporting
confidence: 77%
See 1 more Smart Citation
“…The other azole anti-fungals were all only occasionally detected and at very low concentrations (Table 1). This pattern was similar to that in the water of the Pearl River (Huang et al, 2013). However, the presence of the azole anti-fungals in groundwater has rarely been reported worldwide, precluding further discussion or comparison (Table 1).…”
Section: Azole Anti-fungalssupporting
confidence: 77%
“…Box-and-whisker plots of the PPCPs in the reservoirs in the vicinity of the landfills. See Table 1 also revealed higher PPCP concentrations in wintertime in the Pearl River and suggested that dilution effects play a predominant role in seasonal PPCP patterns in river water (Huang et al, , 2013Peng et al, 2011). However, limited sampling sites in the reservoirs precluded indepth analysis of seasonal effects on the distribution of PPCPs in the reservoirs.…”
Section: Ppcps In the Reservoirsmentioning
confidence: 99%
“…GC-MS/MS was employed in the first works reporting enantioselective environmental analysis by indirect methods using enantiomerically-pure derivatizing reagents [9,60], or by direct methods using CSPs [61,85]. Despite indirect [70,83] and direct methods [67,80,89] remaining in some studies, LC-MS/MS has been the analytical technique of election for illicit drugs and pharmaceutical while GC-MS and GC-ECD have been the most used for pesticides [13,54,55,57,62,[64][65][66][67][68][69][71][72][73][74][75][76][77][80][81][82]84,87,88,[90][91][92]95,[100][101][102][103][104][105]. Although much less used, LC-DAD, LC-UV and LC-FD detection have been used in some of the studies [11,26,27,…”
Section: Basic Concepts Of Chiralitymentioning
confidence: 99%
“…A study focused in the enantioselective determination of azole antifungals showed that these pharmaceuticals were racemic or almost racemic in the raw wastewater (EFs = 0.45-0.53) and a weak enantioselectivity was observed during treatment at WWTP [88]. The EFs of the dissolved antifungals differed from those of the sorbed fraction in the suspended particulate matter, proposing different behaviors for these enantiomers in the two distinct phases of the wastewater.…”
Section: Illicit Drugs and Pharmaceuticalsmentioning
confidence: 99%
“…O mesmo grupo de investigadores estudou os mesmos antifúngicos quirais (excepto propiconazol) em águas residuais e superficiais. 117 Neste estudo, a FE nos afluentes foi globalmente de 0,5, não variando significativamente após tratamento na ETE, mesmo quando as concentrações diminuíram muito, sugerindo uma degradação fracamente enantiosseletiva. Pelo contrário, na matéria particulada das águas residuais, a FE dos antifúngicos foi ligeiramente diferente de 0,5 no afluente e 0,5 após tratamento anaeróbio, sem variação da concentração.…”
Section: Análises Quirais Em Ambiente Realunclassified